2021
DOI: 10.1039/d1fo01144h
|View full text |Cite
|
Sign up to set email alerts
|

Aloe-emodin prevents nerve injury and neuroinflammation caused by ischemic stroke via the PI3K/AKT/mTOR and NF-κB pathway

Abstract: Ischemic stroke (IS) caused by cerebral arterial occlusion is the leading cause of global morbidity and mortality. Cellular oxidative stress and inflammation play a vital role in the pathological process...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 35 publications
0
53
0
Order By: Relevance
“…The PI3K/AKT pathway, including the mammalian target of rapamycin (mTOR), is another important signaling route mediating microglia damage [83,84]. Its activation regulates NF-κB activity in neuroinflammation [85,86].…”
Section: Neuroinflammationmentioning
confidence: 99%
“…The PI3K/AKT pathway, including the mammalian target of rapamycin (mTOR), is another important signaling route mediating microglia damage [83,84]. Its activation regulates NF-κB activity in neuroinflammation [85,86].…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Xian et al found that aloe-emodin significantly improved the infarct size and behavioral score of MCAO rats, decreased the expression of TNFα, MDA, and increased SOD. In vitro, in oxygen and glucose deprivation reperfusion (OGD/R) model of human neuroblastoma cells (SH-SY5Y) and LPS stimulated BV2 cells, AE significantly protected SH-SY5Y cells from the injury of OGD/R and reduced the production of inflammatory cytokines in BV2 cells stimulated by LPS via PI3K/AKT/mTOR and NF-κB signaling pathways [134]. In H2O2-induced apoptosis and neuroinflammation of SH-SY5Y cell, emodin exerted the similar effects on oxidative stress.…”
Section: Cerebral Vascular System and Central Nervous Systemmentioning
confidence: 99%
“…In a middle cerebral occlusion reperfusion rat model, AEM was able to reduce serum TNF-α levels, and protected rats from neurological deficits, suggesting that AEM protected the rats from neuroinflammation [ 51 ]. AEM treatment of LPS-stimulated microglial BV2 cell lines was able to inhibit the production of NO as well as pro-inflammatory cytokines IL-6 and TNF-α.…”
Section: Aloe Compounds For the Regulation Of Immune Respons...mentioning
confidence: 99%